Selah [large type] - Bergren, Lisa Tawn (Bergren, Lisa Tawn. Sugar baron's daughters, 2020)
"When a Methodist preacher, called to serve slaves in the West Indies, settles at Selah's family plantation, their shared purpose brings them together-despite her guardians' concern over a romance that promises little security. As the Revolutionary War and starvation looms in the States, the future hangs in the balance"--Provided by publisher.